Mitochondrial Function as a Potential Tool for Assessing Function, Quality and Adulteration in Medicinal Herbal Teas - Woodley, Steven B.; Mould, Rhys R.; Sahuri-Arisoylu, Meliz; Kalampouka, Ifigeneia; Booker, Anthony; Bell, Jimmy D. (Frontiers in Pharmacology, 2021)
Quality control has been a significant issue in herbal medicine since herbs became widely used to heal. With the advent of modern technologies, evaluating the quality of medicinal herbs has become more sophisticated but so have the methods of adulterating them. In this paper we undertook a comprehensive literature search to identify the key analytical techniques used in the quality assurance of herbal medicine, reviewing their uses and limitations. We also present a new tool, based on mitochondrial profiling, that can be used to measure medicinal herbal quality. Besides being fundamental to the energy metabolism required for most cellular activities, mitochondria play a direct role in cellular signalling, apoptosis, stress responses, inflammation, cancer, ageing, and neurological function, mirroring some of the most common reasons people take herbal medicines. A fingerprint of the specific mitochondrial effects of medicinal herbs can be documented in order to assess their potential efficacy, detect adulterations that modulate these effects and determine the relative potency of batches. Furthermore, through this method it will be possible to assess whole herbs or complex formulas thus avoiding the issues inherent in identifying active ingredients which may be complex or unknown. Thus, while current analytical methods focus on determining the chemical quality of herbal medicines, including adulteration and contamination, mitochondrial functional analysis offers a new way of determining the quality of plant derived products that is more closely linked to the biological activity of a product and its potential clinical effectiveness.